Isolation of Ciprofloxacin and Ceftazidime-Resistant Enterobacterales From Vegetables and River Water Is Strongly Associated With the Season and the Sample Type - Díaz-Gavidia, Constanza; Barría, Carla; Rivas, Lina; García, Patricia; Alvarez, Francisca P.; González-Rocha, Gerardo; Opazo-Capurro, Andrés; Araos, Rafael; Munita, José M.; Cortes, Sandra; Olivares-Pacheco, Jorge; Adell, Aiko D.; et al. (Frontiers in Microbiology, 2021)
The dissemination of antibiotic-resistant bacteria (ARB) from water used for crop irrigation to vegetables is poorly studied. During a year, five farmer markets in a city in Central Chile were visited, and 478 vegetable samples (parsleys, corianders, celeries, lettuces, chards, and beets) were collected. Simultaneously, 32 water samples were collected from two rivers which are used to irrigate the vegetables produced in the area. Resistant Enterobacterales were isolated and identified. Colistin resistance gene mcr-1 and extended spectrum β-lactamases (ESBL) were molecularly detected. The association of environmental factors was evaluated, with the outcomes being the presence of Enterobacterales resistant to four antibiotic families and the presence of multidrug resistance (MDR) phenotypes. Parsley, coriander, and celery showed the highest prevalence of resistant Enterobacterales (41.9% for ciprofloxacin and 18.5% for ceftazidime). A total of 155 isolates were obtained, including Escherichia coli (n=109), Citrobacter sp. (n=20), Enterobacter cloacae complex (n=8), Klebsiella pneumoniae (n=8), and Klebsiella aerogenes (n=1). Resistance to ampicillin (63.2%) and ciprofloxacin (74.2%) was most frequently found; 34.5% of the isolates showed resistance to third-generation cephalosporins, and the MDR phenotype represented 51.6% of the isolates. In two E. coli isolates (1.29%), the gene mcr-1 was found and ESBL genes were found in 23/62 isolates (37%), with blaCTX-M being the most frequently found in 20 isolates (32%). Resistant Enterobacterales isolated during the rainy season were less likely to be MDR as compared to the dry season. Understanding environmental associations represent the first step toward an improved understanding of the public health impact of ARB in vegetables and water.